Between Narcissus and Echo: the Agony of the Subject - Obrigewitsch, Alex (Bollettino Filosofico, 2021)
How to speak of the relation between psychoanalysis and deconstruction? Might the truth of the former be evinced by the very work of the latter, always already at work in the questioning of the subject in the former? Taking up the thought of Maurice Blanchot in confronting the truth of analysis (which Lacan links to myth), this paper aims to disclose this secret truth in its very default, (re)inscribing the fundamental myth of psychoanalysis not as that of Oedipus, but rather that of Narcissus and Echo. In complicating the reflections of Lacan, Leclaire, and Legendre in contestation with themselves through the mirror of Blanchot’s writings, the absent and unspeakable truth of analysis is lured out by a linguistic, abyssal play of mirrors. Thus, perhaps, might the difference between deconstruction and psychoanalysis be seen as echoing or (re)doubling a difference internal to each itself. Keywords: Blanchot, Double, Narcissus, Psychoanalysis, Truth